How the Human Capital Model Explains Why the Gender Wage Gap Narrowed - Solomon W. Polachek (Institute for the Study of Labor (IZA), 2004)
This paper explores secular changes in women?s pay relative to men?s pay. It shows how the human capital model predicts a smaller gender wage gap as male-female lifetime work expectations become more similar. The model explains why relative female wages rose almost unabated from 1890 to the early-1990s in the United States (with the exception of about 1940-1980), and why this relative wage growth tapered off since 1993. In addition to the US, the paper presents evidence from nine other countries using data gleaned from the Luxembourg Income Study (LIS).
Keywords: J3; J2; J7; J1; 330; gender; wages; human capital; secular trends; Ernährung; Haushaltseinkommen; Verbraucherausgaben; Unterernährung; Wirtschaftskrise; Russland